Powerpoint-Based Pop Up Book Media in Fifth Grade Historical Narrative Text Material in Elementary Schools - Fira Bening Akhiraningrum; Kurniana Bektiningsih (MIMBAR PGSD Undiksha, 2023)
The problem was found to be a need for more variety of learning media in the learning process in the classroom, especially the Indonesian language learning content, causing low student interest in learning and difficulty in students understanding the material. This research aims to develop learning media, the suitability of the media, and the effectiveness of Powerpoint-based Pop-Up Book learning media as historical narrative text material for class V elementary schools. This type of research is developed using the ADDIE model. The subjects in this research were class teachers, students, and a team of experts. The data collection method used in this research uses observation, interviews, tests, and questionnaires. The data collection instrument uses a questionnaire sheet. In this research, data analysis techniques used several techniques, namely qualitative descriptive techniques, quantitative descriptive techniques, and inferential statistics. The results of this research were obtained from material expert tests of 96.4%, media experts at 95%, class teacher tests at 95%, and student tests at 91.25%. The results of the effectiveness of the pretest and posttest have increased knowledge competency. The results of the n-gain test stated that the media developed was quite effective for use in teaching and learning activities. It was concluded that the PowerPoint-based Pop-Up Book media on historical narrative text material is very good, effective, and quite suitable for learning and can improve student learning outcomes.